Air gasification of empty fruit bunch: an Aspen Plus model - Hoo, Khoo Kar; Md Said, Mohamad Syazarudin (Elsevier, 2021)
A thermodynamic equilibrium model was developed using Aspen Plus to simulate syngas production from air gasification of empty fruit bunch in a fluidized bed gasifier. The proposed model was used to conduct parametric study on gasification temperature, equivalence ratio, and feedstock particle size. The findings were validated against experimental data. Syngas adjustment was done on homogenous reactions to tune back overprediction of CO and H2 and underprediction of CH4 from the initial equilibrium model. High gasifier temperature in 800–1000 °C increases the heating value and carbon conversion (ηc). Both CO2 composition and ηc increased with ER's increment. The effects of ER are less significant in increasing ηc as compared to temperature. Significant influence is observed on the ηc drop and heating value at PSD range of 0.5–1.0 mm. The optimized lower heating value and higher heating value are 11.11 MJ/Nm3 and 12.18 MJ/Nm3 respectively at T = 1000 °C, ER = 0.15 and PSD < 0.3 mm.